Sustainability assessment of the Liaohe Estuary wetland based on emergy analysis. (December 2020) - Su, Fangli; Liu, Haisheng; Zhu, Dan; Li, Lifeng; Wang, Tieliang
Highlights: The total emergy input in the study area was 307.12 × 10 18 sej. The final value was 332.9 × 10 18 sej, and the intermediate service value was 1980.99 × 10 18 sej. The sustainability index (ESI) of the Liaohe Estuarine Wetland was 0.77. The intermediate-final conversion ratio (EIFC) was 1.18%. Abstract: The sustainability of wetlands, as an ecological system, is a key indicator of its system stability. The sustainability evaluation of wetlands is the basis of management and research. In this study, the ecosystem value and sustainability of the Liaohe Estuary Wetland were evaluated by using emergy analysis and emergy indicators. The results showed that the total input emergy of the Liaohe Estuary Wetland was 307.12 × 10 18 sej, included renewable resources 74.83 × 10 18 sej, nonrenewable resources 103.02 × 10 18 sej and purchased resources 129.27 × 10 18 sej. The final emergy value was 332.9 × 10 18 sej, and the main part was the outputs of 290.28 × 10 18 sej, accounting for 87.19% of the total emergy export. The intermediate service value emergy was 1980.99 × 10 18 sej, of which 90.72% was occupied by biodiversity maintenance value. For the sustainability evaluation of the Liaohe Estuary Wetland, the emergy yield ratio (EYR) was 2.38, the environment loading ratio (ELR) was 3.10, and the emergy sustainability indicator (ESI) was 0.77, the development of the study area was in an unsustainable state. A new index of intermediate-final conversion ratio (EIFC) was established to evaluate the conversion proportion from the intermediate value to the final value. EIFC was 1.18%, which showed that the service potential of wetlands was huge.